Olanzapine-Related Somnambulism: A Systematic Review of Literature and a Case Report of Anorexia Nervosa. Issue 6 (November 2021) - de Filippis, Renato; Guinart, Daniel; Rania, Marianna; Carbone, Elvira Anna; Gaetano, Raffaele; Segura-Garcia, Cristina
Abstract: Background: Somnambulism, or sleepwalking (SW), is one of the most common forms of arousal parasomnias. It is characterized by different complex motor behaviors leading to unwanted movements in bed or walking during sleep. It can be the consequence of psychological stress, abnormal breathing during sleep, high fever, or drug adverse effects. There is evidence of an association between antipsychotic treatment, including olanzapine, and SW. Methods: We present the case of a patient experiencing treatment-resistant anorexia nervosa whose somnambulism re-exacerbated after the addition of a low dose of olanzapine, following the CARE (CAse REport) Statement and Checklist. We also conducted a systematic review of the literature on olanzapine-induced somnambulism following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. PubMed, PsychINFO, and the Cochrane Library databases were independently reviewed up to January 2021 for articles reporting olanzapine-related somnambulism cases, without language or time restriction. Results: We describe a case of somnambulism in a patient initially admitted to our hospital for anorexia nervosa and treated with a low dose of olanzapine. This is the first case of SW induced by olanzapine in eating disorders to be reported. Up-to-date olanzapine-related somnambulism was described in 8 patients experiencing psychiatric disorders (ie, schizophrenia and bipolar disorder). Conclusions: To provide a reliable estimate of incidence and prevalence for olanzapine-related somnambulism, large-scale, pharmacovigilance studies are required, to allow for comparisons of overall clinical characteristics, outcomes, including time to recovery, between different treatment options. Clinician awareness should be enhanced, and attention should be given to such infrequent adverse effects associated with antipsychotics. Abstract : Supplemental digital content is available in the text.